Understanding the Middle East’s Centrality in US Foreign Policy - Gouasmia, Saadia; Elaggoune, Abdelhak (Dirasat: Human and Social Sciences, 2025)
Objectives: This study examines the complex interactions among several factors that shape the strategic role of the Middle East in US foreign policy. It explores how the geopolitical dynamics of the region, oil and energy resources, security issues such as terrorism and regional conflicts, and cultural and ideological influences affect US foreign policy. Methods: The study employed a qualitative research methodology, involving a comprehensive study of literature, documents, and current academic works. Objective analysis was employed to explain the interactions among various factors affecting the centrality of the Middle East in US foreign policy. Results: The geopolitical significance of the Middle East is crucial in influencing US foreign policy due to its strategic location and abundant oil reserves. US involvement in the region is deeply affected by security concerns, especially those related to terrorism and regional conflicts. The United States uses the Middle East as a theater for proxy wars, in addition to political alliances and diplomatic initiatives, all of which play a central role in maintaining regional stability. Furthermore, cultural, religious, and ideological factors significantly influence how the United States makes its policy choices. Conclusions: The Middle East holds significant importance in US foreign policy due to its economic, security, and geopolitical significance. Achieving stability in the region is essential for the continuity of global energy markets and addressing security challenges. Additionally, American diplomatic efforts and understanding of the religious, cultural, and ideological backgrounds are crucial in dealing with the complex geopolitical reality of the Middle East.